2023
DOI: 10.3389/fendo.2022.1034494
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling of hepatic tissues for drug metabolism genes in nonalcoholic fatty liver disease: A study of human and animals

Abstract: BackgroundDrug metabolism genes are involved in the in vivo metabolic processing of drugs. In previous research, we found that a high-fat diet affected the transcript levels of mouse hepatic genes responsible for drug metabolism.AimsOur research intends to discover the drug metabolism genes that are dysregulated at the transcriptome level in nonalcoholic fatty liver disease (NAFLD).MethodsWe analyzed the transcriptome for drug metabolism genes of 35 human liver tissues obtained during laparoscopic cholecystect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Nonetheless, previous studies have shown that the level of gene expression involved in drug metabolism changes in NAFLD patients, affecting pharmacokinetics. [66,67] Therefore, there is much potential for our future research on targeted drugs. To conclude, CD37 and CXCL9 could serve as diagnostic markers for NAFLD, this finding may further provide strong support for comprehensive research on precision therapy of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, previous studies have shown that the level of gene expression involved in drug metabolism changes in NAFLD patients, affecting pharmacokinetics. [66,67] Therefore, there is much potential for our future research on targeted drugs. To conclude, CD37 and CXCL9 could serve as diagnostic markers for NAFLD, this finding may further provide strong support for comprehensive research on precision therapy of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…GSE89632 is a representative dataset for investigation of NAFLD and we used it to obtain the most relevant modular genes for NAFLD (23)(24)(25).First, WGCNA was used for the identification of the most relevant modular genes for NAFLD.b = 26 (scale-free R 2 = 0.85) was selected as the "soft" threshold based on the scale independence and average connectivity (Figure 2A). Then, different colors are chosen to represent 9 gene co-expression ).…”
Section: Key Module Genes In Nafld Samples Were Identified By Wgcnamentioning
confidence: 99%